2016
DOI: 10.1096/fj.201600319r
|View full text |Cite
|
Sign up to set email alerts
|

The kidney‐specific expression of genes can be modulated by the extracellular osmolality

Abstract: With this study, we wanted to prove the hypothesis that the unique extracellular osmolality within the renal medulla modulates a specific gene expression pattern. The physiologic functions of the kidneys are mediated by the segment-specific expression of key proteins. So far, we have limited knowledge about the mechanisms that control this gene expression pattern. The hyperosmolality in the renal medullary interstitium is of major importance as a driving force for urine concentration. We made use of primarily … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
52
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 25 publications
(57 citation statements)
references
References 37 publications
4
52
0
Order By: Relevance
“…Our finding is further supported by a recent functional study, in which extracellular osmolality within the renal medulla up-regulated the expression of RanBP3L. 37 The RANBP3L signal may have also reflect other genes in this locus. For example, a nearby gene, SKP2 encoding S-phase kinase associated protein 2, interacts with p27 and promotes p27 degradation 38 .…”
Section: Discussionsupporting
confidence: 87%
“…Our finding is further supported by a recent functional study, in which extracellular osmolality within the renal medulla up-regulated the expression of RanBP3L. 37 The RANBP3L signal may have also reflect other genes in this locus. For example, a nearby gene, SKP2 encoding S-phase kinase associated protein 2, interacts with p27 and promotes p27 degradation 38 .…”
Section: Discussionsupporting
confidence: 87%
“…Primary cultured IMCD cells were prepared as previously described [16]. Female Wistar rats at the age of 23 months were sacrificed by decapitation and the kidneys were removed.…”
Section: Cell Culturementioning
confidence: 99%
“…Total RNA and cDNA synthesis were performed as described before [16]. Real-time PCR was performed using the SYBR Green PCR Master Mix with the ABI PRISM 7900 Sequence Detection System.…”
Section: Real-time Pcrmentioning
confidence: 99%
“…The effect of hyper-osmolality on gene expression can be reverted by hypo osmotic switch [4]. For example one of the hypertonicity-induced transcripts (0 fragments per kilobase of transcript per million mapped reads (FPKM) at 300 vs. 75 FPKM at 900 mosmol/kg, see Table S1) was the E74-like ETS transcription factor 5 (ELF5).…”
Section: Figure 1 (A)mentioning
confidence: 99%
“…However, as mentioned by Lindgren et al [1], the transcriptional cues that determine segment-specific gene expression patterns are only partly understood. We have recently shown that the unique hypertonicity in the renal inner medulla regulates kidney and nephron-specific gene expression [4]. The group of Prof. Ian Frew showed that deletion of renal expression of the tumor suppressor von Hippel-Lindau (VHL) protein altered the urine concentration capability in mice [5].…”
Section: Introductionmentioning
confidence: 99%